The distribution of power within the EU: perspectives on a Ukrainian accession and a Turkish accession - Werner Kirsch (International Economics and Economic Policy, 2022)
On February 28th, 2022, Ukraine submitted an application concerning accession to the European Union. As Ukraine is already linked to the European Union through an Association Agreement and the Deep and Comprehensive Free Trade Agreement—signed in 2014—there might be a chance for the Ukraine to join the EU within the next decade. With about 41 million inhabitants, Ukraine is a rather large country and the 65% majority requirement under the EU's Qualified Majority Voting rules would give Ukraine some significant power in a future EU28. Herein, it is shown how relative political power indices—as measured by the Banzhaf index—would change in the case of an EU enlargement to allow accession by Ukraine: The large economies would lose power and, surprisingly, many small countries would gain political power. Such perspectives might lead one to reconsider the voting procedures of the Council of the European Union at the EU level in the course of future negotiations on amendments to the Lisbon Treaty. The case of Turkey's accession is also considered as is the case of Montenegro joining the European Union.
Keywords: C0; F0; H0; K0; 330; EU enlargement; Ukraine; Banzhaf index; Power; Majority voting